Dribbling Speed In Basketball Games Reviewed From Students' Anthropometrics - Afif, Marlan; Suwardi, Suwardi; Hudain, Muh. Adnan; Ridwan, Andi; Ishak, Muhammad (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of anthropometric factors on the dribbling speed of students of SMPN 3 Bontomarannu at various grade levels. This study used a quantitative method with a descriptive correlational design. The subjects of the study were 178 students, consisting of 55 7th-grade students (average age 12.29 years), 58 8th-grade students (average age 13.38 years), and 65 9th-grade students (average age 14.14 years). The anthropometric variables measured included body weight, height, leg length, arm length, waist circumference, arm circumference, palm length, palm width, span length, and foot length. Dribbling speed was measured using a dribbling test with recording travel time. Data analysis used multiple regression analysis with a significance level of α = 0.05. The results showed differences in the influence of anthropometrics at each grade level. In grade 7 students, there was no significant effect of anthropometric factors on dribbling speed (R² = 0.126; p > 0.05 for all variables). Grade 8 students also showed insignificant results, even though the correlation value was higher (R = 0.410; R² = 0.168; p > 0.05 for all variables). In contrast, in grade 9 students, a significant effect was found with a strong model (R = 0.627; R² = 0.393). Three anthropometric variables had a significant effect: height had a positive effect (β = 0.164; p = 0.018), leg length had a negative effect (β = -0.204; p = 0.000), and palm width had a negative effect (β = -1.350; p = 0.015). The average dribbling time decreased with increasing grade level, namely 21.57 seconds (grade 7), 20.27 seconds (grade 8), and 17.02 seconds (grade 9). The influence of anthropometric factors on dribbling speed varies based on the level of student maturity. Anthropometric factors did not have a significant effect on students in grades 7 and 8, but had a significant effect on students in grade 9. This shows that with increasing age and physical maturity, anthropometric factors begin to play a role as determinants of dribbling speed. Optimal height, proportional leg length, and appropriate palm width are important factors in the dribbling ability of more mature students.